MOTIVASI BELANJA ULITARIAN PADA SUPERMARKET KOTA BANDUNG (ANALISIS SOSIOLOGI-EKONOMI) - Ria Arifianti; Farah Putri Firsanty (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze utilitarian shopping motivation among supermarket consumers in Bandung City from a socio-economic perspective using James Coleman's Rational Choice Theory. A descriptive qualitative approach was employed. Primary data were collected through in-depth interviews with supermarket consumers selected using snowball sampling. The findings reveal that utilitarian shopping motivation is reflected in two main dimensions: efficiency and achievement. In terms of efficiency, consumers utilize supermarkets and digital shopping applications to save time, effort, and product-search costs. Regarding achievement, consumers seek to fulfill their needs accurately, obtain more economical prices, and complete shopping tasks effectively. The results indicate that utilitarian shopping behavior represents a form of rational action based on cost-benefit calculations. The modern retail structure, characterized by promotional programs, product completeness, and digital services, influences consumer decision-making, while the accumulation of individual rational choices contributes to strengthening the dominance of supermarkets and the digital retail ecosystem in Bandung. Therefore, utilitarian shopping motivation reflects not only consumption behavior but also the dynamic relationship between actors, resources, and urban economic structures.